Singapore’s cultural regimentation & Phillip Jeyaretnam’s disillusionment with grand narratives - Tan, Henryk Damien Abucewicz Yuan-Jue (2015)
The leitmotif of national discourse figures in an entire genre of Singaporean fiction, where many of Jeyaretnam’s contemporaries criticize the directionless cultural landscape that has been constantly misdirected by parochially materialistic developments of modern Singapore – developments that have disrupted the cultivation and crystallization of an autochthonous culture. While Abraham’s Promise too provides incisive commentaries on the Peoples' Action Party's (PAP) governing ideologies, Jeyaretnam ultimately remains suggestively apolitical, if not disillusioned with political narratives, as the novel’s metanarrative concern over the mistrust of grand narratives take centre stage and shows how, after all the plots and sub-plots, the Singaporean ethos should never be terminal.